Frameless Stereotactic Brain Biopsies: Comparison of Minimally Invasive Robot‐Guided and Manual Arm‐Based Technique. Issue 3 (September 2020) - Minchev, Georgi; Kronreif, Gernot; Ptacek, Wolfgang; Kettenbach, Joachim; Micko, Alexander; Wurzer, Ayguel; Maschke, Svenja; Wolfsberger, Stefan
Abstract : BACKGROUND: : Most brain biopsies are still performed with the aid of a navigation‐guided mechanical arm. Due to the manual trajectory alignment without rigid skull contact, frameless aiming devices are prone to considerably lower accuracy. OBJECTIVE: : To compare a novel minimally invasive robot‐guided biopsy technique with rigid skull fixation to a standard frameless manual arm biopsy procedure. METHODS: : Accuracy, procedural duration, diagnostic yield, complication rate, and cosmetic result were retrospectively assessed in 40 consecutive cases of frameless stereotactic biopsies and compared between a minimally invasive robotic technique using the iSYS1 guidance device (iSYS Medizintechnik GmbH) (robot‐guided group [ROB], n = 20) and a manual arm‐based technique (group MAN, n = 20). RESULTS: : Application of the robotic technique resulted in significantly higher accuracy at entry point (group ROB median 1.5 mm [0.4‐3.2 mm] vs manual arm‐based group (MAN) 2.2 mm [0.2‐5.2 mm], P = .019) and at target point (group ROB 1.5 mm [0.4‐2.8 mm] vs group MAN 2.8 mm [1.4‐4.9 mm], P = .001), without increasing incision to suture time (group ROB 30.0 min [20‐45 min vs group MAN 32.5 min [range 20‐60 min], P = .09) and significantly shorter skin incision length (group ROB 16.3 mm [12.7‐23.4 mm] vs group MAN 24.2 mm [18.0‐37.0 mm], P = .008). CONCLUSION: : According to our data, the proposed technique of minimally invasive robot‐guided brain biopsies can improve accuracy without increasing operating time while being equally safe and effective compared to a standard frameless arm‐based manual biopsy technique.